2010
DOI: 10.1258/ijsa.2010.010152
|View full text |Cite
|
Sign up to set email alerts
|

The awareness of postexposure prophylaxis for HIV infection following sexual exposure in emergency departments in a regional HIV network

Abstract: The introduction of UK clinical guidelines in 2006 set clear standards for the provision of postexposure prophylaxis for HIV following sexual exposure (PEPSE) to patients who present to health-care settings. However, some patients have reported wide inequities in provision of PEPSE. We used a questionnaire to evaluate staff awareness and provision of PEPSE in various clinical situations in three major emergency departments (EDs) in the Wessex region of the UK. Thirty-three doctors and 50 nurses completed the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Prior to this community‐based project, in the local region, people could only obtain PEP from emergency rooms (ER), wherein they would receive 3‐day starter packs at the time of their visit, and would be referred to the Infectious Diseases clinic housed in the tertiary care hospital for further assessment and provision of the remaining 25‐day regimen. Problematically, many factors deter people from accessing the ER for PEP after sexual exposure to HIV; for example, wait times, being rushed by staff, staff misunderstanding PEP (e.g., that PEP increases unprotected sex, or is for occupational exposure only), and people's reluctance to discuss their sexual histories with ER staff due to perceptions, or previous experiences, of stigmatization based on sexual orientation (Boudreaux, Friedman, Chansky, & Baumann, ; Rutland, Sundaram, & Mani, ; Toma, Triner, & McNutt, ). Accordingly, during meetings with gay advocacy groups, local AIDS service organizations, HIV specialist clinicians, and public health staff, it was decided that PEP should be made available at two community‐based sexual health clinics—one specifically for MSM—because research identified that local MSM felt comfortable accessing these centers for their sexual health needs.…”
Section: Designing a Pep Program For Ottawa Canadamentioning
confidence: 99%
“…Prior to this community‐based project, in the local region, people could only obtain PEP from emergency rooms (ER), wherein they would receive 3‐day starter packs at the time of their visit, and would be referred to the Infectious Diseases clinic housed in the tertiary care hospital for further assessment and provision of the remaining 25‐day regimen. Problematically, many factors deter people from accessing the ER for PEP after sexual exposure to HIV; for example, wait times, being rushed by staff, staff misunderstanding PEP (e.g., that PEP increases unprotected sex, or is for occupational exposure only), and people's reluctance to discuss their sexual histories with ER staff due to perceptions, or previous experiences, of stigmatization based on sexual orientation (Boudreaux, Friedman, Chansky, & Baumann, ; Rutland, Sundaram, & Mani, ; Toma, Triner, & McNutt, ). Accordingly, during meetings with gay advocacy groups, local AIDS service organizations, HIV specialist clinicians, and public health staff, it was decided that PEP should be made available at two community‐based sexual health clinics—one specifically for MSM—because research identified that local MSM felt comfortable accessing these centers for their sexual health needs.…”
Section: Designing a Pep Program For Ottawa Canadamentioning
confidence: 99%
“…8 Evidence suggests a deficit of knowledge of PEP and its uses for non-occupational exposure in EDs. 27 We hypothesised that despite widespread availability of PEPSE throughout the healthcare system, MSM may experience disparate access to PEPSE in EDs as compared to other groups. We compared access to PEP for two scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Abandonment of follow-up is a common challenge in nPEP delivery; similarly, low threemonth follow-up rates of 22-46% have been observed in other industrialized settings. 7,9,10 These observations, and our finding that 7.0% of those tested at baseline had asymptomatic syphilis, raise concerns about potential undiagnosed HIV and other important infections in this population, despite demonstrated willingness to seek medical attention. Lost opportunities for testing, diagnosis, preventive interventions such as vaccination and linkage to care are serious problems, potentially fuelling ongoing propagation of HIV and STI epidemics, and novel proactive strategies to improve patient follow-up are needed.…”
Section: Discussionmentioning
confidence: 76%